Superconducting properties of barium in three phases under high pressure from first principles - 周大伟 濮春英 宋海珍 李根全 宋金瑶 卢成 包刚 (Chinese physics B, 2013)
Electron-phonon coupling （EPC） in the three high-pressure phases of Ba is investigated using a pseudopotentlal planewave method based on density functional perturbation theory. The calculated values of superconducting critical temperature Tc of Ba-I and Ba-II under pressure are consistent well with the trends observed experimentally. Moreover, Ba-V is found to be superconducting with a maximum Tc exceeding 7.8 K at 45 GPa. With the increase of pressure, the values of Tc increase in Ba I and Ba-Ⅱ but the value of Tc decreases in Ba-V. For Ba-I at pressures below 2 GPa, the increases of logarithmic average frequency Oog and electron-phonon coupling parameters , both contribute to the enhancement of Tc. For all the three phases at pressures above 2 GPa, Tc is found to be primarily determined by Further investigation reveals that for all the three phases, the change in with pressure can be explained mainly by change in the phonon frequency. Thus for Ba-II and Ba-V, although they exhibit completely different superconducting behaviors, their superconductivities have the same origin; the pressure dependence of Tc is determined finally by the pressure dependence of phonon frequency.